Energetic ions during plasma-enhanced atomic layer deposition and their role in tailoring material properties. (28th February 2019) - Faraz, Tahsin; Arts, Karsten; Karwal, Saurabh; Knoops, Harm C M; Kessels, Wilhelmus M M
Abstract: Plasma-enhanced atomic layer deposition (PEALD) has obtained a prominent position in the synthesis of nanoscale films with precise growth control. Apart from the well-established contribution of highly reactive neutral radicals towards film growth in PEALD, the ions generated by the plasma can also play a significant role. In this work, we report on the measurements of ion energy and flux characteristics on grounded and biased substrates during plasma exposure to investigate their role in tailoring material properties. Insights from such measurements are essential toward understanding how a given PEALD process at different operating conditions can be influenced by energetic ions. Ion flux-energy distribution functions (IFEDFs) of reactive plasmas typically used for PEALD (O2, H2, N2 ) were measured in a commercial 200 mm remote inductively coupled plasma ALD system equipped with RF substrate biasing. IFEDFs were obtained using a gridded retarding field energy analyzer and the effect of varying ICP power, pressure and bias conditions on the ion energy and flux characteristics of the three reactive plasmas were investigated. The properties of three material examples—TiO x, HfN x and SiN x —deposited using these plasmas were investigated on the basis of the energy and flux parameters derived from IFEDFs. Material properties were analyzed in terms of the total ion energy dose delivered to a growing film in every ALD cycle, which is a product of the mean ion energy, total ion flux and plasma exposure time. The properties responded differently to the ion energy dose depending on whether it was controlled with RF substrate biasing where ion energy was enhanced, or without any biasing where plasma exposure time was increased. This indicated that material properties were influenced by whether or not ion energies exceeded energy barriers related to physical atom displacement or activation of ion-induced chemical reactions during PEALD. Furthermore, once ion energies were enhanced beyond these threshold barriers with RF substrate biasing, material properties became a function of both the enhanced ion energy and the duration for which the ion energy was enhanced during plasma exposure. These results have led to a better insight into the relation between energetic ions and the ensuing material properties, e.g. by providing energy maps of material properties in terms of the ion energy dose during PEALD. It serves to demonstrate how the measurement and control of ion energy and flux characteristics during PEALD can provide a platform for synthesizing nanoscale films with the desired material properties.